A Novel Ashwagandha (Withania somnifera) Formulation Mitigates Sleep Deprivation-Induced Cognitive Impairment and Oxidative Stress in a Rat Model - Er, Besir; Ozmen, Busra; Sahin, Emre; Orhan, Cemal; Şahin, Nurhan; Morde, Abhijeet A.; Şahin, Kazım (Mdpi, 2025)
Ashwagandha (Withania somnifera) is a well-known adaptogenic herb traditionally used to enhance sleep quality and mitigate stress-induced cognitive decline. This study investigated the effects of different doses of ashwagandha root extract (AE) formulations on cognitive function, oxidative stress, and neuronal plasticity in a rat model of sleep deprivation (SD). Forty-nine rats were randomly assigned to seven groups: control, wide platform (WP), SD, SD + A1 (15 mg/kg AE 1.5%), SD + A2 (30 mg/kg AE 1.5%), SD + A3 (5.5 mg/kg AE 8.0%), and SD + A4 (11 mg/kg AE 8.0%). The extract was administered orally for four weeks. SD induced via a modified wide platform model significantly impaired spatial memory, increased oxidative stress, and suppressed GABA receptor activity. Treatment with all AE doses, except 15 mg/kg AE 1.5%, considerably reduced serum corticosterone (12% for SD + A2, 15% for SD + A3, and 32% for SD + A4), CRH (11% for SD + A2, 14% for SD + A3, and 17% for SD + A4), ACTH (22% for SD + A2, 26% for SD + A3, and 38% for SD + A4), and MDA levels (31% for SD + A2, 34% for SD + A3, and 46% for SD + A4) (p < 0.05). All doses improved antioxidant enzyme activity and memory performance, while AE 8.0% doses notably increased serotonin (19% for SD + A3 and 33% for SD + A4) and dopamine levels (40% for SD + A3 and 50% for SD + A4). Moreover, AE treatment enhanced markers of neuronal plasticity and partially improved GABAergic function. These findings suggest that AE formulations, particularly at higher concentrations, exert neuroprotective effects against SD-induced cognitive impairment by modulating oxidative stress, neurotransmitter balance, and neuroplasticity, indicating their potential application in managing stress-related neurological disorders.
Keywords: ashwagandha; withanolides; memory; sleep deprivation; stress; GABAergic pathway